'Opening the electronic gate': raising spiritual awareness online. Issue 2 (1st September 2011) - Groves, Karen; Baldry, Catherine; Smith, Brian; Sumner, Ken; Rimmer, Dominic
Abstract : Background: Following an audit of spiritual and religious needs assessment and care provision across one cancer network area in the Northwest of England in 2006 it was clear that most health professionals working within specialist palliative care services felt that they lacked confidence, and would benefit from further education, in spiritual support. The cancer network supported the development of an interactive learning package for staff. 'Opening the Spiritual gate', to meet this expressed need. Aims: To raise awareness of the spiritual and religious needs of patients and families To help staff feel more confident in discussing and assessing them. To provide this education in a format which is easily accessible and available to staff. Method: A joint project between a cancer network and a university technology department in the Northwest of England resulted in the conversion of the interactive awareness raising course of four sessions, originally delivered face to face (on one day or as a series), into an online course based on a constructivist learning format. Results: The iterative process involved in the conversion, a description of the online instance and the resulting course along with the qualitative analysis of the pilot are described. The results show that the online platform allowed participants to access the course at a time to suit themselves, from anywhere which had internet access and allowed them to learn at their own pace with time for reflection. Conclusion: Clearly e-learning does not suit everyone, but this project has shown that conversion of even a course reliant on group interaction is possible as long as sufficient material and activity, to meet all learning styles and preferences, is built in and the course is organised to allow small cohorts of people to form a learning community for its duration.